In the diagram above, points through are co-linear and evenly spaced. The curves are five half-ellipses, similar to each other, and terminating in the points through .
At the two red points, the half-ellipses intersect at right angles.
At the two green points, the half-ellipses intersect at angle .
If , where and are coprime positive integers, how much is ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I choose a coordinate system such that A : ( − 2 , 0 ) ; B : ( 0 , 0 ) ; and so on.
Let E 1 be the half-ellipse from A to C; E 2 be the half-ellipse from B to D; E 3 the half-ellipse from B to E. Their equations are ⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ E 1 : E 2 : E 3 : x 2 + b y 2 = 2 2 ( x − 2 ) 2 + b y 2 = 2 2 ( x − 3 ) 2 + b y 2 = 3 2 d x d y = − b y x . d x d y = − b y x − 2 . d x d y = − b y x − 3 . The value of b is the same in each case because the half-ellipses are similar.
By symmetry we know that the intersection of E 1 and E 2 has x = 1 ; thus 1 2 + b y 2 = 2 2 ∴ b y 2 = 3 . Moreover, since E 1 and E 2 are symmetric and intersect at right angles, they must have d y / d x = ± 1 in the intersection point. Substituting this in the equations above we find b y = x = 1 , so that y = 3 and b = 3 1 .
Now for the intersection of E 1 and E 3 . Subtracting their equations, we get ( x − 3 ) 2 − x 2 = 3 2 − 2 2 ∴ x = 3 2 . Substituting this in the equations for E 1 and E 3 we get y = 4 2 / 3 . Thus E 1 and E 3 intersect in ( x , y ) = ( 3 2 , 4 2 / 3 ) .
We will now find tangent vectors: v 1 = ( 1 , d x d y ∣ ∣ ∣ ∣ E 1 ) = ( 1 , − 3 1 ⋅ 4 2 / 3 3 2 ) ∼ ( 4 2 , − 2 3 ) ; v 2 = ( 1 , d x d y ∣ ∣ ∣ ∣ E 2 ) = ( 1 , − 3 1 ⋅ 4 2 / 3 3 2 − 3 ) ∼ ( 4 2 , 7 3 ) . The cosine of the intersection follows from their dot product: cos θ = ∣ v 1 ∣ ∣ v 2 ∣ v 1 ⋅ v 2 = ( ( 4 2 ) 2 + ( 2 3 ) 2 ) ( ( 4 2 ) 2 + ( 7 3 ) 2 ) ( 4 2 ) 2 − 2 3 ⋅ 7 3 = 4 4 ⋅ 1 7 9 3 2 − 4 2 = 4 4 ⋅ 1 7 9 − 1 0 = 1 1 ⋅ 1 7 9 − 5 = − 1 9 6 9 5 . This is the obtuse angle; for the acute angle we drop the negative sign.
Thus the answer is 5 + 1 9 6 9 = 1 9 7 4 .